European School for Interdisciplinary Tinnitus (ESIT): A global research training initiative - Shekhawat, Giriraj; Schonell, Stuart; Schoisswohl, Stefan; Biswas, Roshni; Schiller, Axel; Schlee, Winfried (International Journal for Students as Partners, 2022)
The European School for Interdisciplinary Tinnitus Research (ESIT) is an EU-funded doctoral training network. ESIT is a consortium of 12 universities, over 30 commercial and not‐for‐profit organizations, and 15 PhD students providing cutting-edge education across 10 European countries to develop highly knowledgeable and innovative experts in the field of tinnitus research. The ESIT consortium is composed of multidisciplinary researchers and academics engaged in supervising culturally diverse students from nine countries. Over the span of 4 years, ESIT students demonstrated transformational growth in academic and personal spheres and overcame multiple challenges. This case study documents the meaningful partnerships developed between students and the ESIT support network and some of the challenges faced by ESIT in training 15 international students during a global pandemic. It documents the co-creation of knowledge achieved by those engaged in a global shared learning journey and the conflicts and cultural dimensions that they navigated.